Preparation and characterization of triton-water-diesel nanoemulsion with and without cerium oxide - Salahuddin, Bidita Binte (2014)
Water-in-diesel nanoemulsions are considered as alternative fuels for internal combustion engines, to enhance combustion efficiencies and reduce exhaust emissions. A high energy emulsification process using a range of ultrsonication amplitudes (20 to 35 % with 10 minutes processing time) was employed to prepare nanoemulsion fuels. Nanoemulsion fuels were formulated by using a range of surfactant (Triton X-100) concentrations (0.31 % to 0.49 % w/w) with varying water concentrations (0.80% to 1.15% w/w). Cerium oxide (CeO2) was also incorporated into the nanoemulsion fuels in order to evaluate the effect of fuel additive on the nanoemulsion properties. A screening method was carried out to determine the most suitable experimental conditions for the formation of nanoemulsion fuel in terms of improved combustion and emission properties. The screening process was conducted by analysing the emission of fuels from an engine test bed, namely CO2, CO and NOx. It was found that nanoemulsion fuels have the ability to reduce exhaust emissions compared to that of neat diesel. The exhaust temperature of neat diesel was found to be 290 °C along with the CO2, CO and NO emission concentrations of 21784, 766, and 276 ppm, respectively. A significant reduction of exhaust temperature (up to 33%) as well as NOx emission (up to 61%) was obtained during the combustion of cerium oxide enriched nanoemulsions compared to those without. The physico-chemical properties of screened nanoemulsions such as color, density,fuel stability, kinematic viscosity, flash point, pour point, acid number, calorific value and cetane number were determined and comparison was made to neat diesel. The destabilization methods; mainly Ostwald ripening was discussed to investigate the stability of nanoemulsions. The morphology of the nanoemulsions was studied by using the micrographs obtained from transmission electron microscopy (TEM). The size of the droplets formed in the prepared nanoemulsion fuel was found in the range of 1.5 nm to 74.0 nm. Overall, nanoemulsion fuels show great potential as alternative fuels.